2022
DOI: 10.1097/ju.0000000000002748
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Urine Biomarkers Test in the Diagnosis of Upper Tract Urothelial Carcinoma: Results from a Single-Center Prospective Clinical Trial

Abstract: Study Need and Importance: The correct risk categorization and staging of upper tract urothelial cancer (UTUC) is key for disease management. Computerized tomography urography and urinary cytology have limited accuracy for risk stratification of UTUC. Ureteroscopy (URS) may increase the risk of bladder cancer recurrence. Recently, Bladder EpiCheck TM (EpiCheck) showed a high accuracy in the detection of bladder cancer. The aim of the study is to investigate the diagnostic accuracy of EpiCheck in the clinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The same epigenetic test was used in a prospective study by Territo et al, who reported a sensitivity, specificity, NPV, and PPV of 83%, 79%, 77%, and 84%, respectively, for selective samples obtained from the upper tract. 24 However, “bladder” samples from the same cohort demonstrated lower values, with sensitivity, specificity, NPV, and PPV of 51%, 79%, 77%, and 55%, respectively. Despite these advances, none of the aforementioned methylation panels and urine biomarkers has been validated for use in patients with UTUC.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The same epigenetic test was used in a prospective study by Territo et al, who reported a sensitivity, specificity, NPV, and PPV of 83%, 79%, 77%, and 84%, respectively, for selective samples obtained from the upper tract. 24 However, “bladder” samples from the same cohort demonstrated lower values, with sensitivity, specificity, NPV, and PPV of 51%, 79%, 77%, and 55%, respectively. Despite these advances, none of the aforementioned methylation panels and urine biomarkers has been validated for use in patients with UTUC.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, a few studies have reported the clinical implementation of DNA methylation biomarkers in urine-based UTUC biospecimens. 16,22-24 Monteiro-Reis et al, using the methylation levels of 3 methylation biomarkers (GDF15, TMEFF2, and VIM) in urine samples of 22 UTUCs and 20 controls, reported a sensitivity of 91% and a specificity of 100% for the detection of UTUC. 16 A study of larger combinations of selected genes (CDH1, HSPA2, RASSF1A, TMEFF2, VIM, and GDF15) in the urine samples of 98 UTUC patients and 113 controls identified UTUC with a sensitivity of 82% and a specificity of 68%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another PCR test is Bladder EpiCheck offered by Nucleix. This multiplex DNA methylation-based PCR assay is for monitoring of tumor recurrence in conjunction with cystoscopy in patients previously diagnosed with bladder cancer ( 53 , 54 ). Also in development, Singlera Genomics is recruiting colorectal cancer patients to run clinical trials on their ColonAiQ six-plex methylation PCR test for MRD and cancer recurrence ( 55 ).…”
Section: Mrd Assays: Products On-market Clinical Trials and Emerging ...mentioning
confidence: 99%